If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3d = 5(2 + -9) Combine like terms: 2 + -9 = -7 6 + -3d = 5(-7) Multiply 5 * -7 6 + -3d = -35 Solving 6 + -3d = -35 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -3d = -35 + -6 Combine like terms: 6 + -6 = 0 0 + -3d = -35 + -6 -3d = -35 + -6 Combine like terms: -35 + -6 = -41 -3d = -41 Divide each side by '-3'. d = 13.66666667 Simplifying d = 13.66666667
| -15(0)+3y=9 | | 2x-2=-4+2x | | 100x^4-25=0 | | -(3x-9)+10x= | | 7(2p+6)=56 | | 9-(2x+3)=x | | 15(-1)+3y=9 | | 48=9-x | | 2.25t+5=13.5t+5 | | x^3-2x^2-8x= | | 5Y+Y=1 | | -2x-3y=-13 | | 2.75d-4.5=-2.25d+3.5 | | -8(8-x)=0.8(x+10) | | x-5(1)=3 | | 53=3q | | x-5(0)=3 | | (2u-1)(5-u)=0 | | 10t-10=60 | | x=100-10y | | 16=y(2) | | 6(2x-4)+3=12x-21 | | 5(n+5)=4n | | 3(4-2x)=27 | | 28=4y | | 0=8Q-Q^2 | | x^2+3x+10x+1+5x+4=180 | | 3(x+4)-3=15 | | x-(3x-7)=5x-(x+21) | | 7x-18=45-2x | | 8-5t=3t-24 | | 50=20+3a |